Perancangan Alat Bantu Kerja untuk Mengurangi Risiko Postur Kerja pada Area Perakitan Enclosure Mesin Otomatisasi Berbasis Aluminium Profile di PT XYZ - Naufal Rafii Alfarizi; Andriani; Annisa Syahliantina (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The assembly process of automation machine enclosures based on aluminum profiles at PT XYZ is still performed manually at low working positions, causing workers to frequently adopt bent, squatting, and prolonged sitting postures. These conditions may increase the risk of Musculoskeletal Disorders (MSDs), which can reduce worker comfort and productivity. This study aims to analyze the level of working posture risk in the enclosure assembly area, identify the body parts experiencing the highest level of discomfort, and design a work aid to reduce ergonomic risks. The research employed the Nordic Body Map (NBM) method to identify musculoskeletal complaints and the Rapid Entire Body Assessment (REBA) method assisted by Ergofellow software to evaluate working posture risks. The results indicated that the dominant complaints were experienced in the back, lower back, neck, shoulders, and hands. The REBA assessment produced a score of 7 for the first worker, categorized as a medium risk level, and a score of 8 for the second worker, categorized as a high risk level. Based on these findings, an ergonomic work chair was designed with adjustable height, back support, and wheels to improve work flexibility. The implementation of the proposed work aid is expected to reduce the risk of MSDs, enhance worker comfort, and improve productivity in the enclosure assembly process